Good bad things [videorecording (DVD)] - Stanger, Shane D.; Kennedy, Jessica Parker; Robinson, Samantha, 1991-; Whitney, Ryan (Music Box Films, 2025)
Danny and Jason do everything together: they're best friends, business partners, and even roommates. Danny, who lives with muscular dystrophy, is disillusioned by past relationships and is still hurting over a recent breakup. Despite having supportive friends and family, he feels like something is missing and hopes to open up to love again. As luck would have it, Danny and Jason's design firm is up for a contract with a dating app, which Danny insists he will download for research purposes only, of course! An unexpected match with Madi, an enigmatic photographer, challenges him to be vulnerable and sparks a profound journey of self-acceptance, as Danny discovers and shares the extraordinary beauty of his unique body.